Shehar Khali Koocha Khali (A novel during Corona Virus) Analytical Review - Hasni, Allah Rakha; Bibi, Rizwana; Umar, Muhammad Zahid (sourcecoder, 2024)
International epidemic outbreak has affected the creative unity of writers .A lot of fictional and non fictional work has been done in the context of pandemic days and nights .Gabriel Marquez ,Albert camus,Saleem shehzad,Atzal Murad and many others have made a complete picture of the destroyed and dispersed society that is facing destruction and desperation .Absence of a direct interaction of mankind is a the greatest flaw of pandemic era.Special issues of magazines and journals like as ‘Goshwara’ and ‘Almi Jaiza’ are exemplary works that have been done in the form of a research document .Post –Corona literature is being written till now after the great shocks of pandemic impact. Although more literature is in the form of poetry yet there is also many prose-based writings in regional and national language. Mustansar Husain Tarar is a popular author who has written many travelogues and on other genres of literature.’SHEHER KHALI, KOCHA KHALI’ is a novel that is woven in the context of COVID-19 .It depicts the human nature and anthropological behavior in the pandemic era. It highlights the intrinsic dispersion, extrinsic complexities of human life and its effects on the whole human society. It portrays the variance and evolution of collectivity among humans and as whole, epidemic-formed social interaction of mankind.